William Hogarth, Frederick Antal and Deconstruction - Rykov, Anatolii V. (Actual Problems of Theory and History of Art, 2020)
The article assesses the potential of Post-Structuralism for the decoding of William Hogarth’s artistic strategies. Frederick Antal, the author of the fundamental monograph on Hogarth, investigated someproblems of interpretation of artist’s oeuvre in terms of deconstruction mechanisms (parody, expression,caricature, critique of “grand styles”). His conception of Mannerist, a multi-level art-object, which was not elaborated in his theoretical writings, can be explicated from his art historical studies. In the present article, intuitions of F. Antal, Arnold Hauser, and other theorists are explored in relation to the contemporary Post-Structuralism. The author focuses on Hogarth’s works “Royalty, Episcopacy and Law” (1724) and «Enthusiasm Delineated» (1762). Special attention has been paid to Hogarth’s oil-on-canvas painting «The Bench» (Fitzwilliam Museum, Cambridge) and his engraving of the same title, examining them in the context ofModernist (Odilon Redon, Picasso) and classical (Leonardo, Michelangelo, Magnasco) art. «Deconstruction» in Hogarth’s art is interpreted in relation to approaches characteristic of the eighteenth-century culture (John Locke, Henry Fielding, David Hume, John Gay). The article is a part of the author’s project concerning the investigation of the origins of the avant-garde.
Keywords: William Hogarth; Frederick Antal; Henry Fielding; deconstruction; Post-Structuralism; realism; avant-garde; parody; enthusiasm